The Border-Crossing Women - Suryaningsi Mila (UNHI PRESS, 2021)
This paper examines the application of cross-textual reading on the story of women around Moses in the Qur'an and the Bible by grassroots Muslim and Christian women in the village of Wendewa Utara, Central Sumba. Due to the involvement of women, then I apply the feminist approach to analyze the dynamics of cross-textual reading. During several focus group discussions, cross-textual reading was run smoothly because the participants are bound by kinship ties. They are also rooted in Sumbanese cultural values that reflect Marapu religious values. In other words, Muslim and Christian women are living in a context of socio-religious-cultural hybridity in which their religious identity intermingles with their cultural identity. For this reason, this paper describes a project bringing these women into another space of dialogue through cross-textual reading. In the cross-textual reading, both grassroots Muslim and Christian women are crossing their religious borders by finding resonant commonalities between the two texts, as they explore the affirmative, enriched, and irreconcilable difference as well. Cross-textual reading is a new adventure for both Muslim and Christian women in Wendewa Utara. The participants were enthusiastic because the material readings encourage them to share their problems, joys, hopes, and dreams. By reflecting on the struggle of women around Moses, the participants are committed to supporting one another in their daily life. Accordingly, this model of reading creates a safe space for grassroots Muslim and Christian women to learn from one another for mutual enrichment.